Compression properties of multilayer-connected biaxial weft knitted carbon fiber fabric reinforced composites. (15th April 2016) - Pei, Xiaoyuan; Shang, Bo; Chen, Li; Li, Jialu; Tang, Youhong
Abstract: Three kinds of multilayer-connected biaxial weft knitted (MBWK) fabric reinforced composites are studied here, namely three-layer-connected, four-layer-connected, and five-layer-connected biaxial weft knitted fabrics. The compression properties of the MBWK fabric reinforced composites are characterized in the 0° and 90° directions by different carbon fiber volume fractions ( V f ). Macro-fracture morphology and scanning electron micrograph (SEM) images are used to understand the deformation and failure mechanisms. Experimental results show that in the range of V f, the structure of the reinforcement has significant effects on the compression properties of MBWK fabric reinforced composites. The major failure mode of the composites is shear failure, and the cracking of the composites focuses mainly on the delamination of the fabrics between the groups.